1992
DOI: 10.1111/j.1755-3768.1992.tb08576.x
|View full text |Cite
|
Sign up to set email alerts
|

Tear film profile in Graves' ophthalmopathy

Abstract: Tear film profile was studied in 30 patients with Graves' ophthalmopathy. Tear film pH, fluorescein staining, marginal tear strip and Schimer test values in patients with Graves' ophthalmopathy were comparable with controls, indicating normal tear secretion. Tear film break-up-time (BUT) in late Graves' ophthalmopathy was significantly low suggesting unstable tear film. Rose bengal as well as lissamine green staining intensity scores were significantly high, indicating presence of drying epithelial cells in ea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
48
1
2

Year Published

1997
1997
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(58 citation statements)
references
References 7 publications
4
48
1
2
Order By: Relevance
“…Our results showed that BUT and Schirmer test results were lower in GO patients than healthy controls and were lower in active GO patients than in inactive GO patients. These findings were in accordance with previous studies (3)(4)(5)12). We have found only one study (2) in the literature investigating tear osmolarity in patients with GO.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…Our results showed that BUT and Schirmer test results were lower in GO patients than healthy controls and were lower in active GO patients than in inactive GO patients. These findings were in accordance with previous studies (3)(4)(5)12). We have found only one study (2) in the literature investigating tear osmolarity in patients with GO.…”
Section: Discussionsupporting
confidence: 81%
“…IgG antibody may be responsible for hypertrophy of the extraocular muscles, cellular infiltration of the interstitial tissues, and proliferation of orbital fat and connective tissue (2). Patients with GO have symptoms of ocular discomfort including redness, irritation, and foreign body sensation, which are similar to those observed in dry eye disease (DED) (3)(4)(5). Some methods such as tear break-up time (BUT), Schirmer, and mucus fern tests are used for investigation of DED.…”
Section: Introductionmentioning
confidence: 61%
“…This is inconsistent with the suggestion of abnormal mechanical interaction between the upper eyelid and superior corneal limbus in the pathogenesis of SLKK (Wright 1972). Khurana et al (1992) investigate the tear film function in TAED and found that tear film pH, marginal tear film layer, and results of Schirmer test were normal, but break-up time, Rose Bengal and lisamin green staining were consistent with dry eye. Therefore, it is unlikely that the abnormal morphological changes observed in TAED occur as a result of lacrimal gland involvement and decreased aqueous production.…”
Section: Conjunctival Findingsmentioning
confidence: 99%
“…[2][3][4] The most likely mechanism is the increased evaporation of the tear film in TO patients, resulting in evaporative dry eye (EDE). [2][3][4] This is the result of increase in volume of the orbital contents that push the globe anteriorly and increase the palpebral fissure width. Proptosis (and lid retraction, if present) secondarily causes evaporative loss of the tear film and increases the tear film osmolarity.…”
Section: Introductionmentioning
confidence: 99%